Answer:
7/3
Step-by-step explanation:
f(x) =7/(x+2)
g(x) = (x + 5)^2
f(g(-4))=
First find g(-4)
g(-4) = (-4+5)^2
=(1)^2 =1
Then find f(1)
f(1)= 7/(1+2)
= 7/3
Answer:
A.
Step-by-step explanation:
playing in the garden
Answer:
16.
Step-by-step explanation:
The whole numbers stay the same so it stays as 2. The way they get 30 for the denominator is by multiplying the fraction 1/3 by 10 and 1/5 by 6. So now we have 10/30 and 6/30. Add them together, 10+6=16
Answer:
A
Step-by-step explanation:
It is not B because 7x^2 means multiplying the equation by seven. It isn't C because that would move the graph DOWN seven units. And it's not D because when it is in parenthesis like that, it means that it is a horizontal shift, not vertical.